From policy to practice: Experiences from the ECHO trial following revisions of the WHO medical eligibility criteria for contraceptive use (MEC) guidance on DMPA-IM - Petrus Steyn; Mags Beksinska; Melanie Pleaner; Hui-Zhen Tam; Jenni Smit; Kathy Baisley; Douglas Taylor; Mandisa Singata-Madliki; G. Justus Hofmeyr; Thesla Palanee-Phillips; James N. Kiarie (Elsevier, 2024)
Objectives: In 2017, the World Health Organization (WHO) medical eligibility criteria (MEC) for contraception category for intramuscular depot medroxyprogesterone acetate (DMPA-IM) was changed from MEC category 1 to 2 for women at high risk of HIV acquisition. We assessed the impact of communicating this category change among women in the Evidence for Contraceptive options and HIV Outcomes (ECHO) trial. Study design: ECHO was conducted in eSwatini, Kenya, South Africa and Zambia. Women were randomized (1:1:1) to DMPA-IM, levonorgestrel (LNG) implant or copper intrauterine device (Cu IUD). We compared the hazards of DMPA-IM discontinuation and assessed sexual behavior and DMPA-IM satisfaction before and after MEC category change. Results: In DMPA-IM users there was a decrease in the hazards of discontinuation after the MEC change (hazard ratio 0.37; 95% CI=0.26-0.52, p < 0.001). No evidence of an effect of the MEC change was observed in sexual behaviour outcomes. There was some evidence of an increase in disatisfaction with DMPA-IM immediately after the MEC change, with the odds of women reporting a higher score (more dissatisfied) increasing by 1.38 compared with before the MEC change (95% CI=1.11-1.72). Conclusions: While counseling on possible theoretical risks associated with contraceptive methods in the MEC is an important medical ethical standard, in this study it did not adversely impact continuation or sexual behavior, while there was some evidence on increase in dissatisfaction. There is however a need to monitor how changes in MEC categories are implemented. Implications: Although we found no evidence in this analysis of an effect of the MEC change on any of the sexual behavioral outcomes among women after the change in category, it is still an important medical ethical standard to counsel on possible theoretical risks associated with contraceptive methods. Given the challenges of translating research findings to guidelines and further to counseling messages, evaluation of clinical guidelines implementation is necessary to understand the effects of implementation and to monitor both intended impacts and unintended consequences.